Parents’ Divorce Proneness: The Influence of Adolescent Problem Behaviors and Parental Efficacy - Buehler, Cheryl A. (2011)
Early adolescents’ problem behaviors were examined as predictors of parents’ divorce proneness in a community-based sample of 416 families across a 4-year time span. Using family systems theory, it was hypothesized that adolescents’ problems are linked to parents’ divorce proneness through parents’ lower perceived parenting efficacy. Results indicated that adolescents’ externalizing problems were associated with wives’ increased divorce proneness, but not directly with husbands’ increased divorce proneness. Adolescents’ problem behaviors were linked with husbands’ increased divorce proneness through lower paternal efficacy. In terms of crossover effects, adolescents’ problem behaviors were linked with spouses’ increased divorce proneness through their spouses’ lower parenting efficacy. These results specified the family systems precept of interdependence by explicating transmission patterns across family members and subsystems